2014
DOI: 10.2495/cmem-v2-n4-331-345
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of effusion cooling flow and heat transfer

Abstract: An isothermal and non-isothermal numerical study of effusion cooling fl ow and heat transfer is conducted using a Reynolds-averaged Navier-Stokes (RANS) approach. A Reynolds stress transport (RST) turbulence model is used to predict the fl ow fi eld of a staggered array of 12 rows of effusion holes, each hole inclined at 30° to the fl at plate. The Reynolds number based on the hole diameter and jet exit velocity is 3800. The blowing ratio in both studies is 5. A conjugate heat transfer approach is adopted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…The study reported that wall cooling efficiency rises as the center-to-center spacing of neighbor holes gets smaller or the blowing ratios rises. Walton and Yang [19] argued that in the isothermal case, the Reynolds Stress Transport model can reasonably well predict the penetration, injection, downstream disruption, and lateral interactions of jets. Murray et al [20] experimentally investigated flat effusion plate effectiveness with two holes spacings 3.0D and 5.75D by pressure sensitive paint technique.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported that wall cooling efficiency rises as the center-to-center spacing of neighbor holes gets smaller or the blowing ratios rises. Walton and Yang [19] argued that in the isothermal case, the Reynolds Stress Transport model can reasonably well predict the penetration, injection, downstream disruption, and lateral interactions of jets. Murray et al [20] experimentally investigated flat effusion plate effectiveness with two holes spacings 3.0D and 5.75D by pressure sensitive paint technique.…”
Section: Introductionmentioning
confidence: 99%